Solvation Behaviour of Ions in N,N’-Dimethyl Formamide-Water Mixtures Between 298 and 313 K from Thermodynamic Parameters of Viscous Flow - Dhomne, V.P.; Sinha, S.C.; Sinha, P.C. (Asian Journal of Chemistry, 2010)
Viscosity B-coefficients of Jones-Dole equation for the halides of potassium in dimethyl formamide-water mixtures have been utilised to evaluate the thermodynamic parameters of viscous flow between the temperature range 298 and 313 K, using the method of Nightingale and Benck. Ionic Viscosity B-coefficient as well as ionic thermodynamic parameters of viscous flow are obtained on the basis of the concept that the influence of potassium ion upon the viscous flow phenomenon in DMF-H2O mixtures is approximately equal to that for chloride ion. These ionic data together with their variation with temperature and mole-fraction of DMF in solvent are utilised in understanding qualitatively the ion-solvent interaction. ΔE* ion and ΔS* ion values are found to decrease with temperature as well as mole-fraction of DMF in solvent for halides and monovalent Na+ ion and K+ ion. In case of divalent Ca2+, Sr2+ and Ba2+ ions, ΔS* ions are found to increase with rise of temperature. Ionic activation energy and ionic activation entropy of viscous flow at studied temperatures decreases in the order of Na + > K+ > Ca2+ > Sr2+ > Ba2+ for cations and r-> Br- > Cl- for anions.